Developmental Assessment of Sexual Reproduction inButomus umbellatus(Butomaceae): Male Reproductive Component - FERNANDO, DANILO D.; CASS, DAVID D. (Annals of Botany, 1997)
This report deals with the male reproductive component of Butomus umbellatus and examines pollen development, presentation, viability and germinability, as well as pollen tube growth and penetration into the micropyle. Our developmental assessment presents a comprehensive description of the male reproductive processes in B. umbellatus , describes a variety of developmental irregularities starting with meiosis, and discriminates pre- and post-pollination developmental factors causing reduced male reproductive potential. Developmental irregularities that occur in B. umbellatus include meiotic aberrations, pollen abortion, differences in pollen tube diameter, variations in sizes and frequency of callose plugs, excessive winding of pollen tubes and pollen tube branching. These are apparent under in vitro , glasshouse and field conditions, suggesting that such irregularities are innate and unlikely to be due to environmental or nutritional constraints. The lack of difference between self- and cross-pollinations indicates that the developmental peculiarities observed are not due to self-incompatibility reactions. The low numbers of viable pollen grains or grains with a normal appearance are attributed to meiotic aberrations that most likely affected successful division of uninucleate into binucleate pollen grains and subsequent pollen tube growth patterns. In spite of the differences in pollen tube growth patterns, inconsistent pollen tube penetration and pollen tube branching, many of these tubes end up in the micropyle. Therefore, reduced male reproductive potential in B. umbellatus is largely due to pre-pollination developmental events.